2016
DOI: 10.1186/s12889-016-3338-9
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among partners of pregnant women in Sweden: a cross sectional study

Abstract: BackgroundAntenatal care in Sweden involves a visit in pregnancy week 6–7 for counseling about lifestyle issues, including alcohol. The aim of this study was to investigate alcohol consumption among partners of pregnant women, their motives for changing drinking patterns when becoming a parent and their perceptions of the midwife’s counseling about alcohol.MethodThe study was conducted at 30 antenatal care centers across Sweden in 2009–2010. All partners who accompanied a pregnant women in pregnancy week >17 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…Women are however advised to avoid alcohol around the time of conception and during pregnancy as no safe limit has been established and the effects of fetal alcohol spectrum disorders can be devastating [63, 64]. Nearly three quarters of men in our study continued to drink alcohol during pregnancy but other studies have found that men have given up drinking in support of their partners [46, 65].…”
Section: Discussionmentioning
confidence: 86%
“…Women are however advised to avoid alcohol around the time of conception and during pregnancy as no safe limit has been established and the effects of fetal alcohol spectrum disorders can be devastating [63, 64]. Nearly three quarters of men in our study continued to drink alcohol during pregnancy but other studies have found that men have given up drinking in support of their partners [46, 65].…”
Section: Discussionmentioning
confidence: 86%
“…Pregnancy is also associated with reduction in partner AUD, though to a lesser extent than among mothers. Again, this suggests that factors other than fetal alcohol exposure contribute to the observed association; a previous study found that changing social contexts and concern for the mother motivated decreased alcohol consumption among the partners of pregnant women (35). The discrepancy in risk reduction across mothers and fathers may be attributable to concerns about alcohol's direct effect on the fetus: Brief interventions that educate pregnant women about alcohol's teratogenic effects have been shown to decrease consumption (14,36).…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with the fact that parents of small children are prioritized for advice provision in the national guidelines (9). Further, alcohol screening and conversation is an integrated part of standard Swedish antenatal care, with about 85% of pregnant women (18) and a large proportion of partners to pregnant women (19) being screened with the AUDIT questionnaire at antenatal care visits.…”
Section: Discussionmentioning
confidence: 99%